2022
DOI: 10.1038/s41598-022-24997-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and associated factors in HIV-infected patients receiving antiretroviral treatment in Burundi: a cross-sectional study

Abstract: Currently, the life expectancy of people living with the human immunodeficiency virus (HIV) and the general population are similar. Hypertension is a major public health issue in Africa and is largely underdiagnosed. Most HIV-infected individuals, especially those on Anti-Retroviral Therapy (ART) have hypertension. Our project aims to determine the prevalence of hypertension and associated factors amongst HIV-infected adults treated by ART in Burundi. A cross-sectional study was conducted among HIV-infected su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 43 publications
6
21
1
Order By: Relevance
“…From our study, we observed a prevalence of hypertension among People Living with HIV (PLHIV) at 17.4%. This prevalence aligns closely with ndings from studies conducted in Burundi and Zambia [13,14]. Slightly lower prevalence rates were reported from studies conducted in Ethiopia (14%) and Tanzania (8%) [26,27].…”
supporting
confidence: 89%
See 3 more Smart Citations
“…From our study, we observed a prevalence of hypertension among People Living with HIV (PLHIV) at 17.4%. This prevalence aligns closely with ndings from studies conducted in Burundi and Zambia [13,14]. Slightly lower prevalence rates were reported from studies conducted in Ethiopia (14%) and Tanzania (8%) [26,27].…”
supporting
confidence: 89%
“…Of note is the nding that factors such as the duration of HIV diagnosis, HIV type, viral load, duration on treatment, antiretroviral adherence rate, and antiretroviral regimen were not signi cantly associated with hypertension in our study. Similar ndings have been reported in several studies investigating the association between hypertension and these HIV-related health factors [13,42]. In contrast, some studies have reported associations between hypertension and antiretroviral medication regimens based on Non-Nucleoside Reverse Transcriptase Inhibitors (NNRTIs) and Protease Inhibitors (PIs) [14,43].…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Numerous studies in the last ve years have shown an increase in the prevalence of obesity and overweight among HIV-positive people, particularly in Africa, with a clear correlation to HAART adherence [9]- [15]. Prior research has mostly focused on evaluating how weight affects immune cells in HIVuninfected people, with mixed results.…”
Section: Introductionmentioning
confidence: 99%